Calculation of the Elastic Maximum Transverse Bending Moment of Trapezoidal Corrugated Web Girder - Luo, Hong-guang (Periodica Polytechnica Civil Engineering, 2022)
Trapezoidal corrugated web girder (TCWG) is widely used in many fields. The elastic transverse bending moment which exists in the flange influences the mechanical properties of TCWG. For the simply supported TCWG, the equivalent load method is proposed in this paper. And the transverse bending moment calculation model is established. The calculation formula of the elastic maximum transverse bending moment under the most unfavorable geometrical situation is deduced. The formula is consistent with the existing literature. ANSYS finite element method is used to calculate the elastic transverse bending moment of the flange. The calculation results of formula are in good agreement with the finite element analysis. The existence of transverse bending moment is verified by the experimental data. The physical significance of the transverse bending moment as the integral bearing performance index of the TCWG is revealed in this paper. This paper provides a reference for further analysis of transverse bending moment of simply supported TCWG.